2010
DOI: 10.1007/s12011-010-8737-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vanadium on the Subset and Proliferation of Peripheral Blood T Cells, and Serum Interleukin-2 Content in Broilers

Abstract: The purpose of this 42-day study was to investigate the effects of dietary excess vanadium on immune function by determining changes of the subsets and proliferation function of peripheral blood T cells. Four hundred twenty 1-day-old avian broilers were divided into six groups and fed on a corn-soybean basal diet as control diet or the same diet amended to contain 5, 15, 30, 45, and 60 ppm vanadium supplied as ammonium metavanadate. In comparison with those of the control group, the percentages of CD (3) (+) ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…CD 4 + T cells concentrate in the inter-follicular areas, and both CD 3 + and CD 8 + T cells distribute in the lamina propria and epithelium [17]. In the present study, the percentages of CD 3 + , CD 3 + CD 8 + , and CD 3 + CD 4 + in cecal tonsil were decreased in 45 and 60 mg/kg groups and increased in 5 mg/kg group, which were consistent with the results of our recent studies [18,19]. The results showed that the population and biological function of mature T cells were affected.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…CD 4 + T cells concentrate in the inter-follicular areas, and both CD 3 + and CD 8 + T cells distribute in the lamina propria and epithelium [17]. In the present study, the percentages of CD 3 + , CD 3 + CD 8 + , and CD 3 + CD 4 + in cecal tonsil were decreased in 45 and 60 mg/kg groups and increased in 5 mg/kg group, which were consistent with the results of our recent studies [18,19]. The results showed that the population and biological function of mature T cells were affected.…”
Section: Discussionsupporting
confidence: 93%
“…(2) The cecal tonsil lesions can explain the tissular basis of the decreased T cells. (3) Lesions are observed in the thymus [18]. Thymus is the place where T cells are activated and differentiated to CD 4 or CD 8 T cells, and then mature T cells migrate from thymus to the peripheral blood and secondary immune organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other biological functions of vanadium and vanadium compounds as anti-tumor drugs, anti-parasitic agents and their estrogenic actions, reflecting recently medicinal applications of this element, and their availability and safety for clinical use have also been described recently [6]. In addition, our studies show that excessive vanadium strongly negatively affects the normal cellular immunity [7][8][9][10].…”
Section: Introductionsupporting
confidence: 58%
“…It is reported that in chicken, the CD 4+ T cells are considered as helper/inflammatory T cells which respond to exogenous antigens in conjunction with the class II MHC molecules (Cui et al, ). The CD 8+ T cells are considered as cytotoxic T cells and respond to endogenous antigens in conjunction with the class I MHC molecules (Kannangai et al, ).…”
Section: Discussionmentioning
confidence: 99%